Mikołajek w krainie teologii, czyli miłość do książki u kresu epoki Gutenberga. O twórczości Jerzego Szymika - Mazan-Mazurkiewicz, Alicja (Acta Universitatis Lodziensis. Folia Librorum, 2010)
In Poland Jerzy Szymik is a precursor of a scientific research on literature analysed from a theological perspective and treated as a locus theologicus. Literature and books are topics explored extremely often in the works of Jerzy Szymik, both in his essays, religious articles and poetry. The purpose of this paper is to present the most vital aspects of the topics. Presence of the art of reading as well as joy of reading as a poetic  theme seems to be of a particular interest.